On a Chemoenzymatic Desymmetrization–Ring Expansion Strategy towards Functionalized N-Heterocycles - Thiel, Daniel; Deska, Jan (Synlett, 2013)
The direct combination of the desymmetrization of N-heterocyclic meso-diols using lipase from Mucor miehei as biocatalyst and subsequent ring expansion of the optically active products by activation of the remaining hydroxy group gives rise to functionalized nonsymmetrical piperidines in a highly enantio- and diastereoselective manner.
Keywords: desymmetrization; biocatalysis; ring expansion; heterocycles; azasugars